Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Sikap Etis Mahasiswa Akuntansi (Studi Kasus Pada Perguruan Tinggi Swasta di Kota Bandung) - Pupung Purnamasari; Magnaz Lestira Oktaroza; Elly Halimatusadiah (Jurnal Manajemen Bisnis Performa, 2011)
The researi is aimed at: 1) Testing the effect of emotional intelligence (EQ) , and spiritual intelligence (SQ) on ethical attitudes of university accounting students. Simultaneously and partially: 2) Testing which variable that has dominant effect. The respondents of the research are accounting students at the State University of Parahyangan (UNPAR), Maranatha University (Maranatha), Pasundan University (UNPAS), Bandung Islamic University (UNISBA) and Widyatama University UTAMA in Bandung City. Purposive sampling technique is chosen with criteria respondents have done Auditing I Subject. Data was gathered by questionnaires and documentation. Data analysis to test hypothesis is done with multiple linear regression analysis. This research reauins siows that EQ, and SQ simultaneously and partially had significanuly effect on ethical attitudes of university accounting students SQ has significatly, and dominantly effects on technical attitudes of university accounting students. Key words : EQ, SQ, ethichal attitudes, ethics.